PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII MTs THAMRIN YAHYA RAMBAH HILIR - Murniati, Yusi; Deswita, Hera; -, Arcat (Universitas Pasir Pengaraian, 2015)
The purpose of this research is to know wheter there is the effect of cooperative learning Two Stay Two Stray(TSTS) toward result of studying matematik students. The kind of this research is quasi experimental, with population all the students on 7th grade classs of MTs Thamrin Yahya. The Sampling Technique used was Purposive Sampling technique that consists of two classes was experimental class and control class. In experimental class was applied cooperative learning model of Two Stay Two Stray (TSTS) and for control class was applied conventional learning model. The instrument used was essay. The hypothesis testing used Ttest, got the calculation of result tcant = 3,28 and ttable = 2,0057. This showed that tcant > ttable fact plane 5%. Thus, there was the effect in cooperative learning model Two Stay Two Stray (TSTS) toward the result of studying mathematics.